Antimicrobial Stewardship Activities in Public Healthcare Facilities in South Africa: A Baseline for Future Direction - Deirdré Engler; Johanna Catharina Meyer; Natalie Schellack; Amanj Kurdi; Brian Godman (MDPI AG, 2021)
Antimicrobial resistance (AMR) is a growing problem worldwide, including South Africa, where an AMR National Strategy Framework was implemented to instigate antimicrobial stewardship programmes (ASPs) and improve antimicrobial prescribing across sectors. To address the need to assess progress, a sequential mixed methodology with an explanatory research design was employed. In Phase 1, a self-administered questionnaire was completed by healthcare professionals (HCPs) from 26 public sector healthcare facilities across South Africa to assess compliance with the Framework. The results were explored in Phase 2 through 10 focus group discussions and two in-depth interviews, including 83 participants. Emerging themes indicated that public healthcare facilities across South Africa are facing many challenges, especially at entry level primary healthcare (PHC) facilities, where antimicrobial stewardship activities and ASPs are not yet fully implemented. Improved diagnostics and surveillance data are a major shortcoming at these facilities. Continuous education for HCPs is deficient, especially for the majority of prescribers at PHC level and health campaigns are nearly non-existent. Involvement and visibility of management at certain facilities is a serious shortfall. Consequently, it is important to call attention to the challenges faced with improving antimicrobial prescribing across countries and address these to reduce AMR, especially in PHC facilities, being the first point of access to healthcare for the vast majority of patients in developing countries.